Репресії проти «церковників» і «сектантів» в УРСР, 1917–1939 рр. - Рубльова, Н. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The article is dedicated to the results of political repressions against the clergy and the believers in 1937–1938.